Sulfur functionalized monoliths and particles derived from the same as nitric oxide carriers for pharmaceutical and cosmetic applications
Sulfur-functionalized monoliths and particles address scalability and biocompatibility issues in silica production, enabling cost-effective and efficient NO delivery with enhanced biocompatibility and localized administration.
Patent Information
- Application Number
- JP2024145135
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-06-19
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-17
AI Technical Summary
Existing methods for producing silica particles for drug delivery, such as the Stöber process and its modifications, face challenges in scalability, low yields, and the need for surfactant removal for biocompatibility, while NO delivery systems suffer from enzyme dependence, toxicity, and high costs.
The development of sulfur-functionalized monoliths and particles derived therefrom, which allow for spontaneous NO release without enzyme involvement, are manufactured at lower costs and feature a rough surface for enhanced biocompatibility and localized delivery.
These monoliths and particles provide efficient, cost-effective NO delivery with improved biocompatibility and localized administration, overcoming the limitations of existing technologies.
Smart Images

Figure 2024174904000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. Provisional Application No. 62 / 863,503, having a filing date of June 19, 2019, the disclosure of which is incorporated herein by reference in its entirety. [Background technology]
[0002]
[0002] Ceramic particles, such as silica, alumina and aluminum silicate, are promising drug carriers because ceramics have favorable chemical properties, thermal stability and biocompatibility. In addition, the production of certain ceramics can be achieved by various synthetic routes using different monomers to modify the properties for certain applications. One method for producing silica particles is the Stober process, a nucleation / growth sol-gel method in which hydrolyzable silane precursors react with water in an alcohol solution. However, there are some disadvantages to this method because the conditions may require low concentrations of alkoxysilane monomers, extended reaction times under constant shear with constant and continuous monomer introduction, and incomplete conversion of monomers to particles. The result of the Stober process is small, monodisperse particles, which may be useful for certain applications, but the method has some disadvantages for large-scale production, due in part to long reaction times, low yields and costs.
[0003] Following the discovery of the Stober process, a two-step modification was reported that allows for the patterning of pores in silica particles to produce mesoporous silica particles. Due to the large surface area of the pores, these particles have great potential for applications in drug delivery. Fabrication involves reacting silane precursors with self-assembled hexagonal arrays of cylindrical mesopores. This new method also has drawbacks, including low yields and the need to remove the surfactant to ensure biocompatibility.
[0004]
[0004] The use of silica particles as delivery agents for drugs (e.g. proteins) by conjugation with surface active groups or by loading in the pores has provided a new route for drug delivery with improved disease targeting, reduced side effects and improved patient outcomes. However, there is still room for significant progress to improve manufacturing methods and thereby reduce costs to patients and companies. In addition, the development of carriers for the delivery of certain fugitive small molecules will expand the applications and procedures for which particulate carriers can be used.
[0005] For example, over the past few decades, several nitric oxide (NO)-related therapies have emerged. In general, these systems use enzymatic activity to generate NO from prodrugs. These prodrugs include organic nitrates, most notably nitroglycerin, and organometallic NO donors, such as sodium nitroprusside. Drawbacks such as progressive tachyphylaxis due to exhaustion of the host enzymes required for NO production, potential toxicity from toxic by-products (e.g., sodium nitroprusside decomposes releasing NO as well as cyanide), and short-term biological effects all limit the effectiveness of these treatments. Although gaseous NO is effective and FDA-approved for the treatment of pulmonary hypertension, its use in patients is limited by cost, the need for delivery via gas tanks, and potential toxicity issues due to the production of NO2. Summary of the Invention [Problem to be solved by the invention]
[0006]
[0006] Because NO has a variety of biological uses, including wound healing and disinfection, there is a need in the art for methods and systems that allow for the spontaneous release of NO without the need for enzymatic release or expensive high-pressure storage tanks. [Means for solving the problem]
[0007]
[0007] The present application relates to sulfur-functionalized monoliths and particles derived therefrom as nitric oxide (NO) carriers for use in drug delivery and cosmetic formulations. An exemplary aspect of the present application includes a monolith structure containing a first monomer with sulfur-functionalized side groups that is combined with a second monomer to form a framework. Another aspect of the present application includes particles with rough surfaces derived from the monolith. A further aspect of the present application includes particles with rough surfaces that react to form nitrosylated (e.g., S-nitroso-functionalized) particles containing NO covalently bound to one or more sulfur groups. As described herein, aspects of the present disclosure can include methods for making the monolith structures, methods for obtaining particle(s) with rough surfaces from the monoliths, and methods for treating conditions using nitrosylated particles or NO-loaded particles. In general, embodiments of the present disclosure can provide advantages over other NO delivery systems and methods of manufacture because they can be manufactured at lower cost and exhibit biocompatibility. In addition, the rough surface of the silica particles offers an unexpected advantage as it can embed the carrier particles into the skin and improve NO delivery in applications such as topical administration through increased surface contact.
[0008] A full and enabling disclosure of the present invention, including the best mode thereof, directed to one of ordinary skill in the art, is set forth in other portions of this specification, which include references to the accompanying drawings, in which: [Brief description of the drawings]
[0009] [Figure 1A] 1A-1H are diagrams illustrating monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 1B] 1A-1H show the monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 1C] 1A-1H show the monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 1D]1A-1H show the monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 1E] 1A-1H show the monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 1F] 1A-1H show the monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 1G] 1A-1H show the monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 1H] 1A-1H show the monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 2A]
[0010] 2A-2C show particles formed according to exemplary embodiments of the present disclosure at various magnifications. [Figure 2B] 2A-2C show particles formed according to exemplary embodiments of the present disclosure at various magnifications. [Figure 2C] 2A-2C show particles formed according to exemplary embodiments of the present disclosure at various magnifications. [Diagram 3]
[0011] 1 is a histogram of particle size generated according to an exemplary embodiment of the present disclosure. [Figure 4]
[0012] 4A and 4B are graphs showing instantaneous and cumulative NO release, respectively, according to an exemplary embodiment of the present disclosure. [Figure 5-1]
[0013] 5A-5J show the monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 5-2] 5A-5J show the monolith formation after a reaction time according to an exemplary embodiment of the present disclosure. [Figure 6A]
[0014] 1 is a bar graph showing yield versus condensation time for exemplary embodiments produced at RT or 40° C. [Figure 6B]
[0015] 1 is a bar graph showing average particle size versus condensation time for exemplary embodiments formed at RT or 40° C. [Figure 6C]
[0016] 1 is a bar graph showing NO loading versus condensation time for exemplary embodiments formed at RT or 40° C. [Figure 7A]
[0017] 7A-7C are diagrams illustrating skin tissue in grayscale to which an exemplary embodiment of the present disclosure has been applied. [Figure 7B] 7A-7C are diagrams illustrating skin tissue in grayscale to which an exemplary embodiment of the present disclosure has been applied. [Figure 7C] 7A-7C are diagrams illustrating skin tissue in grayscale to which an exemplary embodiment of the present disclosure has been applied. [Figure 7D]
[0018] 7D to 7F are diagrams showing the images of FIGS. 7A to 7C in color, respectively. [Figure 7E] 7D to 7F are diagrams showing the images of FIGS. 7A to 7C in color, respectively. [Figure 7F] 7D to 7F are diagrams showing the images of FIGS. 7A to 7C in color, respectively. [Figure 8A]
[0019] 8A to 8C are diagrams showing cross sections taken from the tissues shown in FIGS. 7A to 7C, respectively. [Figure 8B] 8A to 8C are diagrams showing cross sections taken from the tissues shown in FIGS. 7A to 7C, respectively. [Figure 8C] 8A to 8C are diagrams showing cross sections taken from the tissues shown in FIGS. 7A to 7C, respectively. [Figure 8D]
[0020] 8D to 8F are diagrams showing the images of FIGS. 8A to 8C in color, respectively. [Figure 8E] 8D to 8F are diagrams showing the images of FIGS. 8A to 8C in color, respectively. [Figure 8F] 8D to 8F are diagrams showing the images of FIGS. 8A to 8C in color, respectively. [Figure 9]
[0021] 1 is a graph showing fluorescence intensity versus strip number for untreated skin control, 1 hour after application, and 6 hours after application. [Figure 10]
[0022] 1 is a graph showing relative pressure versus volume. [Figure 11]
[0023] 1 is a table showing data calculated from a BET analysis of an exemplary embodiment made in accordance with the present disclosure. [Figure 12]
[0024] 1 is a table showing data determined from exemplary embodiments formed using MPTS / TEOS ratios as set forth in the present disclosure. [Figure 13A]
[0025] 13A and 13B are graphs showing ppm of NO and release rate of NO versus time, respectively, according to an exemplary embodiment of the present disclosure. [Figure 13B] 13A and 13B are graphs showing ppm of NO and release rate of NO versus time, respectively, according to an exemplary embodiment of the present disclosure. [Figure 14]
[0026] 14A and 14B are graphs showing ppm of NO versus time, according to an exemplary embodiment of the present disclosure, and release rate of NO versus time, according to an exemplary embodiment of the present disclosure. [Figure 15A]
[0027] 15A and 15B are graphs showing NO release rate and cumulative NO release versus time, respectively, according to an exemplary embodiment of the present disclosure. [Figure 15B] 15A and 15B are graphs showing NO release rate and cumulative NO release versus time, respectively, according to an exemplary embodiment of the present disclosure. [Figure 16]
[0028] 1 is a graph showing cumulative NO release according to an exemplary embodiment of the present disclosure. [Figure 17]
[0029] FIG. 1 shows particles according to the present disclosure collected at the opening of a hair follicle in the skin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010]
[0030] Repeat use of reference characters in the present specification and drawings is intended to represent same or analogous features or elements of the present invention.
[0031] Reference will now be made to embodiments of the invention, one or more examples of which are set forth below. Each example is provided as an explanation of the invention, not a limitation of the invention. Indeed, it will be apparent to those skilled in the art that various modifications and variations can be made in the present invention without departing from the scope or spirit of the invention. For example, features illustrated or described as one embodiment can be used on another embodiment to yield yet a further embodiment. Thus, the present invention is intended to cover such modifications and variations as come within the scope of the appended claims and their equivalents. It should be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments, and is not intended to limit the broader aspects of the invention, which are illustrative embodiments embodied.
[0011]
[0032] In general, the present disclosure relates to sulfur-functionalized monoliths and particles derived therefrom as carriers for pharmaceutical and cosmetic applications. The disclosed materials, compositions, and methods can provide the advantage that their formation occurs rapidly across a variety of conditions, allowing for fast, efficient, and productive manufacturing, which can significantly reduce costs for both manufacturers and consumers. Exemplary embodiments of the present disclosure can include monoliths formed from at least two monomers and containing sulfur functional groups (e.g., thiols), particles derived from the monoliths, methods for making the monoliths, and methods for forming particles from the monoliths. Embodiments of the present disclosure can also include compositions including particles derived from the monoliths, and treatments using the compositions.
[0012]
[0033] For embodiments of the present disclosure, the particles derived from the monolith can carry a compound or a precursor (the precursor converts to a compound upon exposure to conditions). As an example, an embodiment of the present disclosure can include a cosmetic composition containing particles derived from the monolith. In this example, the particles contained in the cosmetic composition can carry a high vapor pressure compound (e.g., NO), which normally exists as a gas under ambient conditions. Nitric oxide is produced by the body and is known to have several biological effects, including increased circulation, which can improve wound healing and also help reduce the effects of aging, such as wrinkles. Thus, application of the composition to an area of the body can provide a means for localized delivery of the compound.
[0013]
[0034] This example illustrates another advantage that can be realized in the practice of embodiments of the present disclosure. In certain embodiments, particles derived from monoliths can have irregular or rough surfaces. Rough surfaces can provide multiple advantages, such as increased surface area for binding to compounds or by embedding in the application area (e.g., upper layers of skin or mucosa). By increasing the surface area, embodiments of the present disclosure can provide improved loading of compounds or precursors, which can reduce the frequency of application. By embedding in the outer surface, these embodiments can improve contact time without requiring the presence of a continuous applicator, e.g., a patch. Because it can be extremely difficult to deliver fugitive compounds, e.g., high vapor pressure diatomic molecules, to a localized area, embodiments of the present disclosure can provide an additional advantage for delivering compounds, e.g., NO.
[0014]
[0035] The particles of the present disclosure are formulated and constructed to be embedded in an external surface, such as the skin of a user. For example, the particles are formed with a high surface roughness, which not only facilitates embedding of the particles in the skin, but also has an optimized particle size for contact with the skin. In one embodiment, the particles have a diameter and shape that allows the particles to congregate at hair follicles in the skin. The hair follicle can act as a funnel for the particles. Once in the hair follicle, the particles are not only protected from removal, but are also located in a place that maximizes the release of the compound or precursor, such as nitric oxide. For example, referring to FIG. 17, human skin (ex vivo human tissue) is shown with the particles of the present disclosure. As shown in the figure, the particles congregate at the hair follicle opening to maximize delivery.
[0015]
[0036] One embodiment of the present disclosure can include a monolith, which includes a first monomer and a second monomer that are bonded to form a framework, and the first monomer includes a sulfur-functionalized side group. Another embodiment of the present disclosure can include a particle derived from the monolith. In general, it is understood that a particle derived from a monolith includes the same chemical composition as the monolith from which it is derived, unless it has been subjected to further reaction or processing. Thus, a particle derived from a monolith also includes a first monomer and a second monomer that include a sulfur-functionalized side group.
[0016]
[0037] In certain embodiments, the first monomer can be present in a molar ratio of about 1:5 to about 5:1 relative to the second monomer, such as about 1:3 to about 3:1 and about 4:6 to about 6:4. References herein are made only to the first monomer, but it should be understood that the other portions need not include only the second monomer. In some embodiments, a third monomer can be present as part of the monolith or monolith-derived particle. In some embodiments, a third monomer and a fourth monomer can be present such that the monolith or monolith-derived particle includes at least four different monomers. As such, embodiments of the present disclosure are not constrained to use only the first monomer and the second monomer.
[0017]
[0038] Generally, the first monomer has Structure I or Structure II
[0018] [ka]
[0019] and each of R1 to R3 independently represents hydrogen (-H); hydroxyl (-OH); halogen (-X) including fluorine (-F), chlorine (-Cl), bromine (-Br), or iodine (-I); a straight or branched chain alkyl group having 1 to 5 carbon atoms, and an alkoxy group having 1 to 5 straight or branched chain carbon atoms (-OC x H y R4 is selected from hydrogen (-H), straight chain or R5 is selected from the group consisting of hydrogen, straight or branched chain alkyl groups having 1-3 carbon atoms, hydroxyl (-OH), thiol (-SH), and halogen (-X), including fluorine (-F), chlorine (-Cl) and bromine (-Br); n and m are independently = 1-4. Substituents not attached to a carbon atom on the phenyl ring (e.g., R5) may be substituted at any position on the phenyl ring.
[0020]
[0039] Exemplary compounds derived from structure I include 3-mercaptopropyl trimethoxysilane (MPTS), 3-mercaptopropyl triethoxysilane (MPTES) and 3-mercaptopropyl methyl dimethoxysilane (MPDMS). These examples are provided for illustrative purposes only and are not intended to limit the scope of the first monomer to only these compounds. In addition, combinations of these compounds or other structures derived from structure I may be included in the monolith or particles derived from the monolith without departing from the spirit and scope of the present disclosure.
[0021]
[0040] Generally, the second monomer comprises the structure III
[0022] [ka]
[0023] Examples of the structure include those derived from the following:
[0041] Exemplary compounds derived from structure III include tetraethyl orthosilicate (TEOS), tetramethyl orthosilicate (TMOS), tetrapropyl orthosilicate (TPOS) and tetrabutyl orthosilicate (TBOS). These examples are provided for illustrative purposes only and are not intended to limit the scope of the second monomer to only these compounds. In addition, combinations of these compounds or other structures derived from structure III may be included in the monolith or particles derived from the monolith without departing from the spirit and scope of the present disclosure.
[0024]
[0042] Although structure III shows a silicate, it is understood that other metal alkoxides, metal oxides and their salts or chelates can be used in embodiments of the present disclosure. For example, in some embodiments, the second monomer can include an alkoxide, salt or chelate of a metal oxide, where the metal is in the group of silicon, aluminum, boron, germanium, barium, lithium, sodium, titanium, zirconium, magnesium, strontium, hafnium and vanadium.
[0025]
[0043] An aspect of certain embodiments can include a third monomer attached to the first and second monomers, either as part of the monolith structure or as part of a particle derived from such a monolith, where the third monomer contains an ionic group. For example, the third monomer can be an anionic organosilane, such as 3-trihydroxysilylpropylmethylphosphonate or 3-((trihydroxysilyl)-1-propanesulfonyl)-2-propanesulfonyl. Examples of suitable charge-containing organosilanes include cationic organosilanes (e.g., aminopropyltrimethoxysilane) or cationic organosilanes (e.g., aminopropyltrimethoxysilane). For these embodiments, the inclusion of a charged group can increase the wettability of the particle, resulting in improved incorporation in certain media, such as compositions with high water content. The inclusion of a charged group can also improve the dispersibility (dispersion) of the particle in water, due at least in part to charge-charge repulsion.
[0026]
[0044] In embodiments of the present disclosure, the monolith or particles derived from the monolith can have a binding capacity for a compound or precursor. In an exemplary embodiment, the compound can include nitric oxide (NO), and the binding capacity for NO can be about 850 to about 3200 nmol of NO per mg of dried monolith or per mg of dried material (e.g., particles) derived from the monolith. In certain embodiments, the binding capacity for NO can be about 1800 to about 1100 nmol of NO per mg of monolith.
[0027]
[0045] For the embodiments of the present disclosure, the compound or precursor may be present as a chemically bound species or a physically absorbed species.As an example, NO may be chemically bound to the sulfur group present on the first monomer to form an S-nitroso bond.The method for preparing the S-nitroso bond is described in more detail in other parts of the present disclosure.
[0028]
[0046] In certain embodiments, monoliths and particles derived from monoliths can include porous structures characterized by pore size and pore volume.In some embodiments, porous structures can be adjusted using different combinations of first and second monomers.For certain applications, the use of porous particles can provide the advantage of having a larger surface area, thereby modifying the binding and / or delivery kinetics of compounds (e.g., NO).
[0029]
[0047] In one embodiment of the present disclosure, the monolith can have a framework that includes a pregel, a gel (e.g., hydrogel), a xerogel, or an aerogel. As used herein, a pregel is meant to describe a precursor to a gel, where a short-range framework begins to form, but the framework is not self-supporting. A pregel can be visually and physically identified using the tests disclosed herein. For example, a pregel typically exhibits precipitation in solution (e.g., cloudiness). A pregel also typically exhibits flow and / or collapse when inverted. A gel can be distinguished from a pregel in that it does not exhibit flow or collapse when inverted, a feature referred to herein as self-supporting. A xerogel refers to a dried gel that can be produced by evaporating a wetting agent from a gel. For hydrogels, the wetting agent includes water, although other wetting agents, such as alcohols (e.g., methanol, ethanol, propanol, etc.), may be present in the gel. Thus, in an embodiment of the present disclosure, the monolith can have a framework that includes a gel, a pregel, a xerogel, and an aerogel.
[0030]
[0048] In embodiments of the present disclosure, particles derived from a monolith can be derived from a monolith having any framework, from multiple monoliths having the same framework, or from multiple monoliths having different frameworks. In addition, particles can be derived from multiple monoliths and then combined to form a mixture of particles derived from different monoliths.
[0031]
[0049] Generally, particles derived from monoliths exhibit physical characteristics that allow them to be distinguished from nucleated particles. For example, particles derived from monoliths can include particles having a rough surface. As used herein, a rough surface refers to a surface having a roughness on the scale of about 0.1 μm to about 3 μm, e.g., about 0.4 μm to about 2.5 μm, about 0.8 μm, each extending from the particle surface. In some embodiments, the particles having a rough surface can include particles derived from a monolith.
[0032]
[0050] The rough surface of a particle can be indicated by the BET surface area of the particle. Particles with greater roughness will generally have a higher BET surface area. The particles of the present disclosure may have a roughness of, for example, about 5 m 2 / g, e.g., about 7m 2 / g, e.g., about 9m 2 / g, e.g., about 11m 2 / g, e.g., about 13m 2 / g, e.g., about 15m 2 / g, generally about 100m 2 The nanoparticles may have a BET surface area of less than 1 / g.
[0033]
[0051] Exemplary embodiments of the particles disclosed herein, including particles derived from monoliths and particles having rough surfaces, include particle sizes of about 0.1 to about 100 microns. The average particle size can be, for example, greater than about 0.5 microns, for example greater than about 1 micron, for example greater than about 1.5 microns, and generally less than about 80 microns, for example less than 60 microns, for example less than 40 microns, for example less than about 30 microns, for example less than about 20 microns, for example less than about 10 microns, for example less than about 8 microns, for example less than about 5 microns. The particle size can be measured using any suitable light scattering or laser method. In addition, these particles include a first monomer as well as a second monomer as described in the monolith embodiment.
[0034]
[0052] In an exemplary embodiment, the plurality of particles can include a group of particles each having a rough surface. In certain embodiments, the group of particles can be polydisperse. Alternatively, in some embodiments, the group of particles can be monodisperse. To achieve a certain size range or particle distribution, in some embodiments, the particles derived from the monolith can undergo additional processing, such as milling using a horizontal bead mill. For example, a planetary ball mill or a horizontal bead mill can be used to wet-mill the particles. Wet milling involves mixing the particles with a suitable liquid (typically water, alcohol or a water / alcohol mix, which in some cases can also include an acid, base or buffer to adjust the pH to improve milling efficiency) in a milling chamber with milling beads (the chamber and beads are typically a compatible material with high density and high hardness, such as ZrO2, and the diameter of the beads ranges from 0.1 to 1 mm). The high speed rotation of the milling chamber creates high impact forces to reduce the particle size to the submicron range. Smaller beads and longer milling times produce smaller particles. For some applications, the particles may be milled down to a diameter of about 100 nm or less.
[0035]
[0053] An exemplary method for determining the polydispersity for a mixture of particles includes Equation 1, where:
[0036]
number
[0037] is calculated using the standard deviation (SD) and mean particle size (mean) as shown below:
[0038]
number
[0039]
[0054] By increasing the surface area relative to the particle mass, particle size adjustment can be used to modify the loading capacity of the particles. Particle size can also affect the penetration of the particles into the skin. Thus, for some embodiments, the method for forming the particles may also include grinding the particles to adjust the average particle size (e.g., to reduce the average particle size).
[0040]
[0055] In another exemplary embodiment, the particle(s) having a rough surface can include a density of sulfur groups from about 1500 μmol to about 3000 μmol per mg of particle.
[0056] Additional embodiments of the present disclosure can include methods for producing monoliths. These methods can include hydrolyzing a first monomer in a solution having a pH less than or equal to 7, providing a second monomer to the solution, reacting the first monomer and the second monomer at a reaction temperature for a reaction time, and providing a base to the solution at the end of the reaction time, where providing the base to the solution increases the pH of the solution to a final pH greater than the starting pH.
[0041]
[0057] Generally, the first and second monomers can include the disclosed first and second monomers that form a monolith structure. For example, the first monomer can include a structure derived from Structure I or Structure II, and the second monomer can include a structure derived from Structure III. In addition, the ratio of the first monomer to the second monomer can include the ratios disclosed as forming a monolith structure. For example, the first monomer can be present in a ratio of 1:5 to about 5:1, or a ratio of about 1:4 to about 4:1.
[0042]
[0058] Exemplary embodiments of hydrolyzing the first monomer in solution can include the concentration and solvent of the first monomer. Some non-limiting examples of solvents that can be included in the solution to produce a monolith include water; alcohol (e.g., methanol); straight or branched alkanes (e.g., hexane); dimethylsulfoxide (DMSO); dimethylformamide (DMF); tetrahydrofuran (THF); benzene; toluene; and any combination thereof. In addition, the first monomer concentration can be between about 5 vol% and about 20 vol%, for example, about 7 vol% to about 15 vol% or about 9 vol% to about 12 vol%.
[0043]
[0059] In an embodiment of the present disclosure, the method for producing the monolith can be carried out at a starting pH of less than or equal to about 6. In one exemplary embodiment, the method for producing the monolith can be carried out at a starting pH of less than or equal to about 3. In another exemplary embodiment, the starting pH can be less than or equal to about 2.
[0044]
[0060] In an embodiment of the present disclosure, a method for producing a monolith can include providing a base to increase the pH to a final pH greater than or equal to about 6. In one exemplary embodiment, the final pH can be greater than or equal to about 7. In another exemplary embodiment, the final pH can be greater than or equal to about 10. can be equal to it.
[0045]
[0061] In an embodiment of the present disclosure, the method for producing a monolith can be carried out at a reaction temperature of about 25° C. to about 80° C. For example, an exemplary embodiment of the present disclosure can include a method for producing a monolith, in which the reaction of a first monomer with a second monomer occurs at a reaction temperature between about 33° C. to about 60° C. Additionally or alternatively, the method for producing a monolith can be carried out at a reaction time of about 0.5 hours to about 8 hours. For example, an exemplary embodiment of the present disclosure can include reacting a first monomer and a second monomer for a reaction time of about 1 hour to about 5 hours.
[0046]
[0062] In an exemplary embodiment, the method for producing a monolith may further include using an inversion test to determine the reaction time. For this implementation, the inversion test may include reacting the first monomer and the second monomer in a reaction vessel for a period of time, inverting the reaction vessel when the period of time is reached, and determining whether a self-supporting structure has formed based at least in part on whether the monolith is retained in the reaction vessel when inverting the reaction vessel. In certain implementations, it may be useful to perform the inversion test iteratively to determine whether the period of time may be longer or shorter. For these implementations, determining whether a self-supporting structure has formed may include a determination based on whether the monolith is retained during inversion. If the monolith is retained, the period of time may be reduced and the inversion test may be repeated. If not (i.e., if the monolith is not retained), the period of time may be increased and the inversion test may be repeated. In some implementations, the number of iterations may be set. In some implementations, the number of iterations may be based on convergence (e.g., if the period was increased in the previous iteration and the period is reduced in the current iteration, the test has converged). Additionally, the amount by which the period is increased or decreased may be fixed or may vary, and thus is not intended to be limited to only a single value.
[0047]
[0063] Another embodiment of the present disclosure can include a method for forming a plurality of particles, each having a roughened surface, comprising mechanically disrupting a three-dimensional structure comprising a first monomer and a second monomer that are bonded to form a framework.
[0048]
[0064] For certain implementations, the step of mechanically disrupting the three-dimensional structure may include vortexing a solution containing the three-dimensional structure, polishing the three-dimensional structure in either gel form in solution or xerogel form not in solution, or a combination thereof. As an example, a monolith gel formed in a solution as described in the exemplary embodiments herein may be vortexed to form a plurality of polydisperse particles. As used herein, vortexing may be achieved by a device or apparatus that can generate a flow in the solution to agitate the solution in contact with the monolith. As used herein, polishing may be achieved by a device or apparatus that directly contacts the monolith to disrupt or modify the three-dimensional structure. Thus, disrupting the three-dimensional structure does not necessarily require direct contact with the monolith, but may include agitating a fluid surrounding the monolith and / or applying a force directly to the monolith itself.
[0049]
[0065] Generally, the step of mechanically disrupting the three-dimensional structure results in a polydisperse mixture of particles with rough surfaces. In certain implementations, it may be advantageous to separate the polydisperse particles to form a group of monodisperse particles, each with a rough surface. Exemplary methods for separating the polydisperse mixture may include sedimentation, which may be used in combination with a fluid flow to transport the lighter particles further along the direction of the fluid flow relative to the heavier particles. Additionally or alternatively, a method may be used to separate the polydisperse mixture by using a method having size selective holes. Sieves can be used to separate polydispersed mixtures.
[0050]
[0066] Another exemplary embodiment of the present disclosure includes a method for loading particles having a rough surface. An exemplary embodiment for loading particles having a rough surface can include providing a plurality of particles from a monolith to a compound or precursor, which upon exposure to conditions undergoes conversion to a compound.
[0051]
[0067] In implementations for loading onto particles having a rough surface, the particles may be in a solution containing a compound or precursor. In certain implementations, the concentration of the compound or precursor may be about 5 wt% to about 30 wt%. In one exemplary implementation, the concentration of the compound or precursor may be about 10 wt% to about 15 wt%.
[0052]
[0068] In addition, one aspect of the loading on the particles having a rough surface can include the loading temperature. In one exemplary implementation, the loading temperature can be between about 0°C and about 40°C. In another exemplary implementation, the loading temperature can be between about 15°C and about 25°C.
[0053]
[0069] In another embodiment of the present disclosure, the precursor can be a nitrite or a nitrite-containing compound. Some non-limiting examples of nitrite or a nitrite-containing compound can include nitroglycerin or a nitrite salt, such as sodium nitrite or potassium nitrite.
[0054]
[0070] In one embodiment of the present disclosure, the conditions for converting the precursor to the compound can include an acid. In one implementation, the acid can include an organic acid (e.g., glycolic acid, acetic acid, tartaric acid, or lactic acid). Additionally or alternatively, the acid can include an inorganic acid (e.g., hydrochloric acid, sulfuric acid, phosphoric acid, etc.).
[0055]
[0071] Another exemplary embodiment of the present disclosure includes a pharmaceutical and / or cosmetic composition comprising a medium containing a plurality of particles loaded with a compound or precursor. In an exemplary embodiment, the plurality of particles loaded with a compound or precursor can be formed from particles derived from a monolith as described in an embodiment of the present disclosure. In certain implementations, the medium can include petroleum products. Some non-limiting examples of petroleum products include methylparaben, mineral oil, isopropyl myristate, white petrolatum, emulsifying wax, and propylparaben, or combinations thereof. Additionally or alternatively, in some implementations, the medium can include natural products. Some non-limiting examples of natural products include beeswax, soy wax, oils derived from plants, cellulose, guar gum, and combinations thereof.
[0056]
[0072] In some implementations, the medium can further include water and a surfactant. In certain implementations, the surfactant can be anionic, cationic, zwitterionic, nonionic, or a combination thereof. Some non-limiting examples of nonionic surfactants that can be used in embodiments of the present disclosure include alcohols (e.g., 1-octanol), fatty acids (e.g., palmitic acid), and fatty acid esters (e.g., glycerol monostearate).
[0057]
[0073] Another exemplary embodiment of the present disclosure includes a method for delivering a compound to a localized region. In one exemplary implementation, the method for delivering a compound to a localized region can be used to treat a patient who has a disease or has been diagnosed with a disorder. For example, one embodiment of the present disclosure can include a method for treating a patient who has been diagnosed with a disorder, comprising administering a composition containing a plurality of particles having a rough surface to a localized region of the patient. In one exemplary implementation, administering the composition to the localized region can be performed by administering a composition containing a plurality of particles having a rough surface to the localized region of the patient. The compound or precursor can be loaded onto a plurality of particles to cause release of the compound. In certain implementations, the release is substantially immediate, such that at least 50% of the compound is delivered in less than 60 seconds. In some implementations, the release is sustained, such that at least 50% of the compound is delivered in less than 300 seconds.
[0058]
[0074] To achieve substantially immediate release, an enhancer can be used in conjunction with administration of a composition containing a plurality of particles loaded with the compound.
[0075] In general, the embodiments of the present disclosure can be combined or used in conjunction with other embodiments disclosed herein.For example, a composition containing a plurality of particles having rough surfaces can include particles derived from a monolith, the monolith including a first monomer and a second monomer.In addition, the particles can be loaded using any of the methods described to include a compound or precursor that can be physically or chemically associated with a portion of the particles.
[0059]
[0076] In one exemplary implementation, the local area may include a part of the patient's body, such as the skin (e.g., face, torso, limbs, hands, nails, and feet) and / or mucous membranes (e.g., mouth, sinuses, rectum, and vagina). Although some particles may migrate or otherwise be removed from the local area, aspects of certain embodiments of the present disclosure may result in improved retention of the majority of particles. For example, compositions including particles with rough surfaces may be embedded into the surface of soft tissue, which may provide benefits for treating local rather than systemic disorders and diseases, or for providing antimicrobial agents to the site of infection or contamination.
[0060]
[0077] In an embodiment of the present disclosure including a method for delivering a compound, the particle having a rough surface can further include a release rate for the compound, thereby delivering a predetermined amount of the compound over time. In one exemplary implementation, the amount of the compound can be released over a period of time. For example, 85% of the compound can be released after 36 hours. Thus, for this example, the amount of the compound is 85% relative to the amount contained in the particle prior to administration, and the period of time is 36 hours. In an embodiment of the present disclosure, the amount of the compound can be about 5% to about 100% (full delivery), and the period of time can be about 0.5 hours to about 36 hours.
[0061]
[0078] In some cases, the release rate can be modified or adjusted using the release conditions. For example, Figures 4A and 4B show graphs showing the immediate release of NO and the cumulative release of NO, respectively. These graphs were determined under accelerated conditions (e.g., exposure to light, acid and / or heat) and in aqueous solutions. In contrast, Figures 13A, 13B, 15A and 15B were obtained using physiologically relevant conditions.
[0062]
[0079] In some embodiments, delivering the compound can include using a plurality of particles with rough surface to deliver NO.For example, an exemplary embodiment can include administering to the patient a composition containing a plurality of particles loaded with NO and having a release rate such that 85% of NO is released after about 36 hours.Another exemplary embodiment can include administering to the patient a composition containing a plurality of particles loaded with NO and having a release rate such that at least 50% of NO is released after about 10 hours.An additional exemplary embodiment can include administering to the patient a composition containing a plurality of particles loaded with NO and having a release rate such that at least 25% of NO is released after about 3 hours.
[0063]
[0080] Certain benefits may be realized by administering the particles to sites including the skin or mucosa without the need for the use of a patch. In general, the particles described herein can be delivered to a subject by a variety of local or systemic delivery routes, including, but not limited to, transdermal, inhalation, oral, local injection, and intravenous introduction. The particles can be administered in a variety of ways, such as, for example, creams. The composition may be incorporated into a cosmetic preparation, ointment, transdermal patch, implantable biomedical device, or scrub.
[0064]
[0081] An additional aspect of the present disclosure may include a method for treating an infection in a subject, comprising administering to the subject a particle loaded with NO or a composition comprising the same in an amount and manner effective to treat the infection. Depending on the site of infection, the particle may be administered locally or systemically.
[0065]
[0082] The term "infection" is used to include infections that can result in infectious diseases. Infectious diseases can include contagious diseases and contagious diseases. As used herein, treating an infection can mean eliminating the infection, reducing the size of the infection, preventing the infection from spreading in a subject, or reducing the further spread of the infection in a subject.
[0066]
[0083] The infection can be, for example, a bacterial, viral, fungal or parasitic infection. The bacterial infection can be a Staphylococcal infection. The bacterial infection can be, for example, caused by bacteria such as S. aureus, multidrug-resistant or methicillin-resistant S. aureus (MRS A), P. aeruginosa, B. circulans, B. cerius, E. coli, P. vulgaris, P. acnes, S. pyognenus, S. enterica, V. angulillarum, K. pneumoniae, P. piscicida, P. aeruginosa, A. tumefaciens, C. micgiganence, A. mali, E. chourysanthemi, X. campestris, C. diplodiella, P. piricoloa, M. tuberculosis and M. ulcerans. Fungal infections can be caused by fungi, such as T. equinum, C. albicans, F. oxysporum, R. solani, B. cinereal, T. rubrum and A. flavus. Viral infections can be caused by viruses, such as M. contagiosum, Rota, Papilloma, Parvo and Varicella. Parasitic infections can be caused by parasites of the genera Plasmodium, Leishmania, Schistosoma, Austrobilharzia, Heterobilharzia, Ornithobilharzia or Cryptosporidium, such as P. falciparum.
[0067]
[0084] An additional aspect of the present disclosure can include a method for promoting angiogenesis, vasodilation, smooth muscle relaxation, wound healing, erectile function, or hair growth in a subject, comprising administering to the subject a particle loaded with NO, or a composition comprising the same, in an amount and manner effective to promote angiogenesis, vasodilation, smooth muscle relaxation, wound healing, erectile function, or hair growth.
[0068]
[0085] A further aspect of the disclosure may include a method for treating a disease or disorder in a subject, comprising administering to the subject a particle loaded with NO, or a composition comprising the same, in an amount effective to treat hypertension, peripheral vascular disease, platelet aggregation, erectile dysfunction, ischemia, inflammation, wounds, abscesses, scleroderma, and sickle cell anemia.
[0069] Example 1
[0086] Example 1 discusses various methods and procedures and provides exemplary embodiments that can be understood in conjunction with the figures and descriptions provided herein. It is understood that the present disclosure is not limited to the examples provided, and the conditions and materials disclosed are exemplary.
[0070] method Two-pot silica gel monolith synthesis
[0087] Silica sol-gel monoliths containing mercaptopropyl functional groups were synthesized by independent hydrolysis of the silica monomers tetraethoxysilane (TEOS) and 3-mercaptopropyltrimethoxysilane (MPTS), followed by monomer condensation to form a spanning network. Following condensation, the monoliths were dispersed into separate silica particles by application of a vortex mixer at a high setting (this mixing step is referred to below as "vortex" or "vortexing"). In this example, the mole % of MPTS is 37.4% (remainder TEOS), but sol-gel monoliths of different mechanical properties can be formed with mole % of MPTS ranging from 5% to 80% (remainder TEOS). Variation of monolith strength in this manner can be employed as a way to affect the particle conversion process to obtain different average particle sizes and size distributions.
[0071]
[0088] Because the MPTS and TEOS hydrolysis reactions proceed for different lengths of time, the initiation of each reaction was timed so that both hydrolysis reactions were completed at the same time. The MPTS hydrolysis was initiated by combining the following: 3.2 milliliters (ml) of methanol; 0.655 ml of deionized (DI) H2O; 0.153 ml of 0.1N hydrochloric acid (HCl); and 0.4 ml of MPTS and vortexed to mix thoroughly. The MPTS hydrolysis reaction was allowed to proceed undisturbed for 90 minutes at room temperature (RT). The TEOS hydrolysis was initiated 30 minutes after the MPTS hydrolysis was initiated by combining the following in a separate container: 1.24 ml of absolute ethanol; 0.655 ml of DI H2O; 0.073 ml of 0.1N HCl; and 0.8 mL of TEOS and vortexed to mix thoroughly. The TEOS hydrolysis reaction was allowed to proceed undisturbed for 60 minutes at RT. The completion of each hydrolysis reaction was simultaneous. At the end of hydrolysis, the MPTS and TEOS hydrolysates were combined and vortexed to mix. Condensation (sol-gel monolith cross-linked network formation) was then initiated by adding 5.8 ml of sodium phosphate buffer (0.1 M, pH 7.4) and mixing thoroughly by vortexing. The monolith cross-linked network formed after approximately 5 min, as evidenced by a color change from clear to cloudy to opaque white (Figure 1A-D). The vessel containing the sol-gel monolith was transferred to a 40°C water bath 15 min after the start of condensation and kept there undisturbed for 4 h until condensation was complete. The silica sol-gel monolith was subsequently dispersed into particles by vortexing to break up the gel, converting the material into a viscous particle suspension (Figure 1G-H). The dispersed particles were washed three times with deionized H2O by dispersing in water and vacuum filtering in a Buchner funnel equipped with Whatman grade 1 filter paper. However, washing of the particles is optional. After the third filtration, the product was dried under vacuum at room temperature for at least 2 hours or until completely dry as indicated by no change in weight over a 30 minute period. After drying was complete, the product was recovered from the filter paper and weighed to assess yield, and subsequently stored at RT until characterization or use.
[0072]
[0089] The synthesized silica particles were characterized in several ways. Scanning electron microscopy (SEM) was utilized to visualize the particle morphology and determine the approximate diameter (Figures 2A-2C). The SEM images showed aggregated particles with a relatively narrow size distribution and irregular circular but not spherical morphology. It is noted that these particles further disperse upon resuspension. The particle size distribution of the hydrated and dispersed particles was quantitatively determined using a laser diffraction particle size analyzer (Beckman Coulter LS 13 320), which showed an average particle size of around 3 μm (Figure 3). Nitric oxide (NO) capacity was determined by mixing the dispersed particles with a molar equivalent of sodium nitrite and 1 molar of hydrochloric acid to form R-SNO groups on the particles, which were subsequently measured on an EcoPhysics CLD60 chemiluminescence NO analyzer. The loading of NO was determined as moles of NO released per mg of particle. The NO release profile and cumulative release curves are shown in Figures 4A-4B. The total N The O loading efficiency was determined to be 50-63% of the theoretical thiol loading, or up to about 2.8 μmol of NO per mg of particle. A listing of relevant values for particle size, yield, and NO loading for four batches of SNO particle synthesis can be found in Table 1.
[0073] [Table 1]
[0074] One-pot silica gel synthesis
[0090] The amounts and conditions of the reagents were the same as those described in the two-pot silica gel synthesis, except that the reagents for TEOS hydrolysis were added directly to the vessel where the hydrolysis of MPTS was proceeding, and the phosphate buffer was added directly to this vessel to initiate the condensation. With 37.4% MPTS (remainder TEOS), the one-pot synthesis produced silica particles with similar yield, particle size distribution, and S-nitrosation efficiency to those synthesized by the two-pot synthesis approach. The average values for yield, particle size, and NO capacity for n=3 batches of each of the two-pot and one-pot syntheses are compared in Table 2. This shows that the one-pot approach can be employed in the synthesis of silica sol-gel monoliths to produce mercaptopropyl-functionalized particles with properties similar to the standard two-pot approach.
[0075] [Table 2]
[0076] Varying Condensation / Gel Aging Time and Temperature
[0091] The sol-gel condensation / aging time was deliberately varied to affect the stiffness of the sol-gel monoliths and the resulting yield, particle size, and sol-gel condensation time at two condensation temperatures, room temperature and 40°C. and its effect on NO loading capacity was determined. Mercaptopropyl-functionalized silica sol-gel monoliths were synthesized using the two-pot procedure described in Example 1, except that the condensation / gel time was systematically varied from 30 min to 96 h and was performed at room temperature (RT) or 40° C. The sol-gel monoliths were formed and condensation was allowed to proceed for the following times before dispersion into particles: 30 min, 1 h, 90 min, 2 h, 4 h, 24 h, 96 h. Gel stiffness was assessed at each time point by inverting the vessel containing the monolith and observing whether the gel remained floating at the bottom of the tube. At each time point, the gel was dispersed, washed / filtered, and dried prior to analysis. Condensation at RT produced a noticeably stiffer gel than condensation at 40° C., which was most evident at the early condensation times, but was noticeable at all time points (FIGS. 5A-5J). Condensation at 40°C produced a gel even after 30 minutes of condensation, but the gel was not rigid and did not remain floating at the top of the tube up to 4 hours of condensation time. Even for condensations longer than 4 hours, minimal shaking of the tube was sufficient to cause the gel to fall off, indicating a weaker gel.
[0077]
[0092] The particle yield was high from the early condensation times and increased slightly with condensation time to about 95% (Figure 6A). Particle size analysis showed that for both condensation temperatures, the particle size decreased with condensation time until it reached a plateau at around 3 μm in diameter (Figure 6B). Notably, this plateau was achieved at 40 °C with a much shorter condensation time than RT, indicating that particle size and gel stiffness change with condensation time, but stiffer gels do not necessarily yield smaller particles. In addition, analysis of NO loading and release showed that the loading of NO increased with condensation time with a plateau close to 2.8 μmol NO / mg of particles (Figure 6C). Similar to the particle size, this plateau was achieved at 40 °C with a shorter condensation time than RT, indicating that the condensation temperature can affect the loading of NO. The results of NO loading, consistent with the literature, indicated that gel aging is a dynamic process and that the fraction of MPTS that becomes incorporated into the gel before disintegration into particles continues to change over time. Data on size statistics, yield and nitric oxide loading are summarized for all samples in Table 3.
[0078] [Table 3]
[0079] Effect of MPTS / TEOS ratio on the properties of sol-gel monoliths
[0093] The range of MPTS / TEOS ratios over which sol-gel monoliths form and the properties of the resulting monoliths were investigated. Sol-gel monoliths were synthesized by a two-pot synthesis according to Example 1, but with varying ratios of MPTS to TEOS. The mole % of MPTS was varied from 10% to 80% (the remainder was TEOS). Sol-gel monoliths formed for mole percentages of MPTS from 0 to 60% were evaluated. MPTS fractions from 0 to 30% produced stiffer, more transparent sol-gel monoliths that did not disperse upon vortex mixing. The color became increasingly transparent as the MPTS fraction was reduced. MPTS fractions from 37 to 60% produced opaque white sol-gel monoliths of various stiffnesses, which decreased with increasing MPTS. It is noted that only MPTS fractions from 35 to 40% formed typical relatively stiff sol-gels, while increasing MPTS fractions produced denser but weaker gels.
[0080]
[0094] The monoliths were dispersed into particles by different methods depending on the characteristics of each monolith. Sol-gel monoliths in the range of 37-60% MPTS that formed opaque white monoliths were dispersed by vortexing and washed / filtered three times before drying. Monoliths that formed hard, more transparent gels could not be dispersed by vortexing alone. The 0-10% MPTS fraction was manually disrupted with a spatula before rinsing and drying. The 20-30% MPTS fraction required the addition of deionized (DI) H2O and shaking before vortexing to disperse. Sol-gels with the MPTS fraction that did not produce monoliths were also mixed by vortexing, then washed three times and dried.
[0081]
[0095] FIG. 11 contains the results of the characterization of the resulting particles. The yields for EOS ratio were calculated and found to be similarly high regardless of the monolith properties. However, the particle size varied significantly. For the more rigid monoliths, the particle size was larger (about 250 μm) and the particles derived from the monolith showed a more granular and glassy character. In the MPTS / TEOS range where no monoliths formed (MPTS>60%), the resulting product was dense and sticky and did not disperse into particles and was not further analyzed.
[0082]
[0096] The NO loading and nitrosation efficiency were also evaluated. The NO loading increased with increasing MPTS fraction in the range of 5-40% MPTS, but then decreased above 40. This indicates that the MPTS / TEOS ratio can be selected to achieve different monolith and resulting particle properties, which also translates to differential NO loading.
[0083] NO release using simulated skin conditions
[0097] To simulate the diffusion that would occur when topically applied, the release of NO from a composition containing particles loaded with NO was evaluated. For this simulation, a composition containing dry particles loaded with NO was incorporated into a petroleum vehicle. The composition contained dry S-nitrosated particles mixed with an anhydrous petrolatum delivery vehicle, with the particles present at 25% by weight of the composition. The composition was then placed in a 6 cm 2 The solution was immediately applied to a piece of wax paper with a surface area of 100 μg / ml and spread thinly to simulate topical application. The wax paper was then transferred to a sampling chamber maintained at 34°C to monitor the release of NO. The sampling chamber was isolated from external lighting and placed under a high-precision LED microscope white light lamp (AmScope LED-6WD) with adjustable settings, and lux was measured using a digital lux meter (Dr.Meter, model: LX1010B). Nitric oxide levels were measured every minute for a period of 60 hours.
[0084] Release of NO in aqueous conditions
[0098] To simulate alternative delivery routes, such as intravenous administration, the release of NO in aqueous conditions was evaluated. For this, a 50 mg aliquot of S-nitrosated particles was added to 5 mL of phosphate buffer in a sampling chamber at 37° C. connected to a nitric oxide analyzer. Nitric oxide levels were measured every 30 seconds for a 12-hour period.
[0085] result
[0099] The results shown in the figures and described herein are meant to be illustrative and are not intended to limit the methods and compositions to modifications or alternatives that would be appreciated by one of ordinary skill in the art of the effort.
[0086]
[0100] Reference is now made to Figures 1A-1H, which illustrate the progression of sol-gel monolith condensation. Images shown are (A) 1 min, (B) 3 min, (C) 5 min, and (D) 10 min after the start of condensation. At the end of condensation (4 h, 40°C), the sol-gel monolith is opaque white and retains in the tube when inverted (E-F). Disintegration of the sol-gel by vortexing disperses the monolith into particles (G-H), which assume a liquid form.
[0087]
[0101] Reference is now made to Figures 2A-2C, which illustrate scanning electron microscope (SEM) images of particles derived from the monolith. The images are shown at various magnifications, including (A) 1500x, (B) 4000x, and (C) 60000x. The particles shown in the images are irregular and exhibit rough surfaces including approximately micron-scale protrusions.
[0088]
[0102] Reference is now made to FIG. 3, which shows data characterizing exemplary particles derived from the monolith. The graph shows a size distribution from 0.017 μm to 2000 μm. Further, the distribution has a mean diameter of 2.956 μm and a median diameter of 2.561 with a standard deviation (SD) of 2.030 μm. , the lower 10th percentile at 0.661 μm, the 50th percentile at 2.561 μm, and the upper 90th percentile at 5.901 μm.
[0089]
[0103] Referring now to Figures 4A and 4B, the graphs shown show exemplary release profiles measuring (A) instantaneous NO release (ppm) and (B) cumulative NO release (nmol / mg of particles) for representative nitrosylated silica particles derived from a monolith. These release profiles were obtained under accelerated conditions in solution using heat and light. For these graphs, after the samples were prepared, the solutions were placed in a chamber for monitoring NO concentration. The chamber was illuminated with bright white light and the temperature of the chamber was maintained at 70°C.
[0090]
[0104] 5A-5J, the images shown show photographs of the progression of the sol-gel monolith over time at (A-E) 0° C. or (F-J) 40° C. Based on inversion testing, the gel solidifies more rapidly at room temperature than at 40° C.
[0091]
[0105] Referring now to Figures 6A-6C, graphs are shown showing (A) yield of silica particles as a function of condensation time and temperature, (B) diameter as a function of condensation time and temperature, and (C) NO capacity of S-nitrosylated particles prepared using different condensation times and temperatures.
[0092]
[0106] 7A-7C, the images shown show grayscale images of whole skin illustrating the application of a petroleum-based medium containing fluorescently labeled silica particles onto cadaveric human skin for (A) medium alone and (B-C) medium with sulfur-functionalized silica particles. Figures 7D-7F show Figures 7A-7C in color, respectively.
[0093]
[0107] Referring now to Figures 8A-8C, the images shown show tissue cross-sections for the samples shown in Figures 7A-C, respectively, showing skin penetration in (A) bright field, (B) fluorescence, and (C) an overlay of Figures 8B and 8C. Figures 8D-8F show Figures 8A-8C, respectively, in color.
[0094]
[0108] Referring now to FIG. 9, the image shows a graph tracking the fluorescence intensity for fluorescently labeled silica particles derived from a monolith applied to human skin. The graph measured the detectable fluorescence after the skin area received several rounds of tape stripping. Although application and removal of the tape strip can reduce the fluorescein, the data shows that the fluorescently labeled particles can still be detected after 10 rounds of tape stripping, indicating some particle embedding in the upper layers of the skin.
[0095]
[0109] Referring now to Figure 10, an image shows a BET analysis on silica nanoparticles derived from a monolith. The analysis was performed using an Autosorb® iQ Station 1 device using nitrogen gas. Further information regarding Figure 10 is included in Figure 11, which includes a summary of data reduction parameters, multi-point BET data and a summary.
[0096]
[0110] Referring now to FIG. 12, an image shows a table providing information characterizing particles formed from monoliths made using the ratios of MPTS / TEOS shown in the table.
[0111] Reference is now made to Figures 13A and 13B, which images respectively show the concentration in ppm of NO and the release rate of NO versus time following a single application of 150 mg of ointment containing 25 wt% particles loaded with NO. As shown, the release shows an approximately exponential decrease, with detectable concentrations of NO even after 48 hours. Figures 14A and 14B show that continuous application of freshly prepared ointment every 24 hours for up to 144 hours results in a significant reduction in the release of NO. A graph is shown showing that the release profile can be reproduced, and this trend can likely be reproduced over as many applications as necessary. Although these experiments are performed with freshly prepared ointments, after the nitrosated particles are incorporated into the ointment, the ointment can be stored in a freezer maintained at 0° C. for at least 3 months without significant loss of NO.
[0097]
[0112] 15A and 15B, which images show graphs illustrating the release rate and cumulative release of NO as measured using the conditions described in the Release of NO Using Simulated Skin Conditions section of the Methods. The graphs show that under physiologically relevant conditions, controlled release of NO can be achieved over an extended period of time, with the majority of NO (over 50%) being released within the first 12 hours.
[0098]
[0113] Referring now to Figure 16, an image shows a graph illustrating cumulative NO release as measured using the conditions described in the Methods: Release of NO in Aqueous Conditions section. The graph shows that NO release is faster in solution compared to topical administration, with the majority of NO (over 50%) being released within the first 3 hours.
Claims
1. 1. A pharmaceutical composition comprising a medium containing a plurality of particles loaded with nitric oxide or a precursor for forming nitric oxide, said plurality of particles comprising: A pharmaceutical composition comprising at least one particle having a rough surface and a functional group, said rough surface comprising a plurality of protrusions each having a size of about 0.01 μm to 2 μm.
2. 10. The pharmaceutical composition of claim 1, wherein the medium comprises a petroleum product.
3. 3. The pharmaceutical composition of claim 2, wherein the petroleum product comprises a product from the group consisting of methylparaben, mineral oil, isopropyl myristate, white petrolatum, emulsifying wax and propylparaben.
4. The pharmaceutical composition according to claim 1 , wherein the vehicle further comprises water and an emulsifier.
5. 5. The pharmaceutical composition of claim 4, wherein the emulsifier comprises an alcohol, an anionic surfactant, a cationic surfactant, a zwitterionic surfactant, or a combination thereof.
6. 6. The pharmaceutical composition of claim 1, wherein at least one particle having a rough surface is derived from disintegrating a monolith.
7. 7. The pharmaceutical composition of claim 1, wherein the at least one particle having a rough surface and functional groups comprises a first monomer and a second monomer that are bonded to form a matrix having a surface area.
8. The first monomer has the chemical structure [Formula 1] wherein each of R1, R2, and R3 is independently hydrogen, a straight or branched chain alkyl group having 1 to 5 carbon atoms, or an alkoxy group having 1 to 5 straight or branched chain carbon atoms; R4 is selected from the group consisting of a hydrogen atom, a straight or branched chain alkyl group having 1 to 4 carbon atoms, and n=1 to 4. The pharmaceutical composition of claim 7, comprising:
9. the second monomer having the chemical structure [Case 2] wherein each of R1-R4 is independently selected from hydrogen or a branched or straight chain alkyl group having 1-5 carbon atoms.
9. The pharmaceutical composition according to any one of claims 7 to 8, comprising:
10. The pharmaceutical composition of claim 1 , wherein the functional group comprises a thiol.
11. 11. The pharmaceutical composition of claim 1, comprising a plurality of particles loaded with nitric oxide or a precursor for forming nitric oxide, the plurality of particles comprising at least 5.0 wt. % and at most 33.0 wt. % of the total weight of the pharmaceutical composition.
12. 12. The pharmaceutical composition of claim 1, wherein the plurality of particles has a nitric oxide binding capacity of about 100 nmol or more and about 1800 nmol or less per milligram of the plurality of particles.
13. 1. A method for treating a patient diagnosed with a disorder, comprising: administering a composition containing a plurality of particles loaded with nitric oxide or a precursor for forming nitric oxide to an administration site in a patient in need of said treatment; A method wherein at least a portion of the particles have a rough surface that causes the particles to embed at the administration site.
14. 14. The method of claim 13, wherein the administration site is the skin of the patient.
15. 15. The method of any one of claims 13 to 14, wherein the compound is released over a period of time.
16. 16. The method of claim 15, wherein at least 85% of the compound is released after 36 hours.
17. 16. The method of claim 15, wherein at least 50% of the compound is released after 10 hours.
18. the plurality of particles carrying the precursor; 18. The method of any one of claims 13 to 17, further comprising the step of delivering a second compound that reacts with the first compound to produce nitric oxide.
19. 19. The method of any one of claims 13 to 18, which does not include the step of applying a coating to the administration site.
20. a polydisperse plurality of particles having an average particle size of about 1 μm to about 8 μm, The particles have a rough surface and functional groups, the particles being about 9 mm in diameter. 2 / g, A polydisperse plurality of particles, wherein the plurality of particles is derived from disintegrating a monolith comprising a first monomer and a second monomer that are bonded to form a framework.
21. 21. The polydisperse plurality of particles of claim 20, wherein the rough surface comprises a plurality of protrusions each having a size of about 0.1 μm to about 2 μm.
Citation Information
Patent Citations
Percutaneous agent and oral agent using silica porous material of nanostructure as carrier
JP2006193462A
Spherical silica whose surface is organomodified and method for producing the same
JP2013010645A
Nanoparticle delivery vehicle for s-nitroso-n-acetyl cysteine and uses thereof
US20150147396A1
Nitric oxide-releasing s-nitrosothiol-modified silica particles and methods of making the same
WO2012118819A2
